Participatory Accountability in Savings and Loan Cooperatives: An Interpretive Phenomenological Study in East Lombok - Yusma, Lalu Nova Saza (Lembaga Penelitian Universitas YARSI, 2026)
Savings and Loan Cooperatives play a vital role in promoting community-based economic development in Indonesia, yet many particularly in rural areas face governance and accountability challenges, including limited transparency, low member participation, and inadequate financial literacy. This study explores the meaning of participatory accountability in cooperative management practices in East Lombok Regency. Using a qualitative design with an interpretive phenomenological approach, the research captures the lived experiences of administrators, supervisors, and members through in-depth interviews, analyzed using phenomenological thematic analysis. The findings show that accountability is not merely compliance with financial reporting standards or regulatory obligations. Rather, it is a socially constructed practice shaped by managerial morality and integrity, dependence on leadership figures, formal governance through Annual Member Meetings (RAT), family-based internal monitoring, limited accounting literacy, symbolic participation, and internal social responsibility reflected in employee welfare. These results suggest that Agency Theory alone is insufficient; a more comprehensive understanding requires integrating Stewardship Theory and Signalling Theory. The study contributes by framing accountability as a value-based social practice embedded in local organizational contexts and offers insights for strengthening sustainable cooperative governance.